2015
DOI: 10.1007/s00284-015-0848-0
|View full text |Cite
|
Sign up to set email alerts
|

New Comparative Analysis Based on the Secondary Structure of SSU-rRNA Gene Reveals the Evolutionary Trend and the Family-Genus Characters of Mobilida (Ciliophora, Peritrichia)

Abstract: In order to reveal the structural evolutionary trend of Mobilida ciliates, twenty-six SSU-rRNA sequences of mobilid species, including seven ones newly sequenced in the present work, were used for comparative phylogenic analysis based on the RNA secondary structure. The research results indicate that all the secondary structures except domains Helix 10, Helix 12, and Helix 37 could be regarded as the criterions in classification between the family Trichodinidae and Urceolariida, and four regions including Heli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Previous studies indicated that some important regions of the SSU rDNA secondary structure could be used for the identification of Mobilida ciliates (Tang et al 2013b;Zhang et al 2015). In the present study, the comparative analysis of the secondary structures revealed distinct differences in H12, H15, E10_1 regions, especially in the V4 region (Fig.…”
Section: Molecular Identification Inferred From Ssu Rdnasupporting
confidence: 62%
See 3 more Smart Citations
“…Previous studies indicated that some important regions of the SSU rDNA secondary structure could be used for the identification of Mobilida ciliates (Tang et al 2013b;Zhang et al 2015). In the present study, the comparative analysis of the secondary structures revealed distinct differences in H12, H15, E10_1 regions, especially in the V4 region (Fig.…”
Section: Molecular Identification Inferred From Ssu Rdnasupporting
confidence: 62%
“…; Zhang et al. ). In the present study, the comparative analysis of the secondary structures revealed distinct differences in H12, H15, E10_1 regions, especially in the V4 region (Fig.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The predicted secondary structures, based on free energy minimization, were constructed for the selected species using RNA structure 5.2 with default settings. The obtained structures were displayed and manually adjusted using RNAViz 2.0 ( Zhang et al 2015 ). Three hypervariable regions of SSU rRNA (V4, V6 and V7) were selected to study their variability.…”
Section: Methodsmentioning
confidence: 99%